STUDI TENTANG FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS STRATEGI BERSAING UNTUK MENINGKATKAN KINERJA PERUSAHAAN PADA KUKM PENGRAJIN KULIT DI MANDING - BANJUL - Barokah, Siti Nur (Magister Manajemen, Fakultas Ekonomika dan Bisnis Undip, 2009)
In a context of enhancing the competitive advantage, acquiring knowledge is an important factor This point is the weakest of the KUKM powerlessness. The problem that Group of Small Business and Entrepreneurs often face basically is on the decision making onCompetitive Strategy in order to enhance the firms' performance. Therefore, it is necessary to examine